Visual impairment, the braille system and educational inclusion from an intersectional perspective - Sandra Milena Sánchez-Medina (Universidad Central de Venezuela, 2020)
This study aimed to assess the reading processes of visually impaired students after a pedagogical intervention that was carried out at the Colegio Técnico José Felix Restrepo, located in Bogotá (Colombia), where eight of these students were chosen from basic and middle education levels between 2017 and 2018. The investigation is qualitative in nature, based on southern epistemologies, and the Test de análisis de lectura y escritura (TALE) was used as an instrument (adapted to the braille system), as well as participant observation, field diaries, and the educational sequence called Braillectura. The methodological design involved different stages such as: a preparatory phase, a reflexive stage, the design stage, the actual field work stage, and the reporting stage. After the pedagogical intervention, it was evident that there were some significant changes regarding the use that is given to the braille system in education. Keywords: Visual impairment; writing; inclusion; intersectionality; reading; braille system.